2017
DOI: 10.1177/1534735417699513
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Behavior After a Diagnosis of Lung Cancer Differs Between Countries: An Observational Cohort Study

Abstract: Introduction. Physical activity (PA) is important in lung cancer. Objectives. To investigate PA levels and health-related quality of life (HRQoL) of patients with lung cancer in China and compare this to a similar cohort in Australia. Methods. Prospective cohort study. 71 patients from China (group CH) and 90 patients from Australia (group AU) with newly diagnosed lung cancer. Questionnaires assessed self-reported PA levels and HRQoL at baseline (diagnosis) and 8 weeks. Results. At baseline, group CH were enga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
1
0
0
Order By: Relevance
“…5 This phenomenon may be explained by the fact that elderly people in China prefer walking as their main transportation while in Western countries driving by the elderly may be more common. 33 The hospital length of stay post-surgery observed in our study was similar to that previously reported in Western countries (8 [7][8][9][10][11][12][13] days). 34 Twenty-one percent of eligible participants who were contacted about the study consented to participation.…”
Section: Discussionsupporting
confidence: 90%
“…5 This phenomenon may be explained by the fact that elderly people in China prefer walking as their main transportation while in Western countries driving by the elderly may be more common. 33 The hospital length of stay post-surgery observed in our study was similar to that previously reported in Western countries (8 [7][8][9][10][11][12][13] days). 34 Twenty-one percent of eligible participants who were contacted about the study consented to participation.…”
Section: Discussionsupporting
confidence: 90%